FEASIBILITY STUDY OF HEDGING POWER GENERATION IN TULEHU GEOTHERMAL FIELD USING BITCOIN MINING - Andriana, Rian
The Tulehu geothermal field is a moderate enthalpy water-dominated geothermal prospect which is currently in the feasibility study stage. According to RUPTL 2021-2030, this field is planned to be built with a capacity of 20 MW. Meanwhile, JICA (2011) states that the existing reserves can reach 30 MW, so that around 10 MW can still be used for other purposes. From the developer's point of view, maximizing the use of potential will be more attractive, however, the additional capacity must be aligned with the demand for electricity in the area. In the case of the Tulehu geothermal field in Maluku which is located in a remote area, the slow growth in demand for electricity is a challenge that requires new businesses to absorb the excess electricity. Cryptocurrency mining or bitcoin mining in particular can be a solution to absorb this excess electricity. The stages used in this research are firstly determining the development strategy, analyzing the economics of power generation and bitcoin mining, modeling bitcoin mining prices, determining the optimal electricity distribution scenario for bitcoin mining and the community and feasibility comparisons between schemes. Based on the results of this study, bitcoin price predictions are made for the next 30 years. Assuming an increase in the difficulty of bitcoin mining into three types, namely, a minimum where the price analysis ignores the effect of the halving, then the most likely (base case) and the maximum which gives a halving effect in the bitcoin price simulation. The optimal scenario is analyzed with the most likely scheme to get the result of 20 MW of electricity distribution for PLN and 10 MW used for bitcoin mining with use for 15 years. After that, the 10 MW will be returned to PLN to anticipate increased demand. The resulting IRR value exceeds 12% in the most likely and maximum possibilities, while in the minimal results, the analysis results are not feasible. The conclusion obtained, the bitcoin mining business is able to make the Tulehu geothermal field development project feasible if the predictions that occur in the bitcoin price are at the most likely and maximum possibility.